Landscape response to late Pleistocene climate change in NW Argentina: Sediment flux modulated by basin geometry and connectivity - Schildgen, T. F.; Robinson, R. A. J.; Savi, S.; Phillips, W. M.; Spencer, Joel Q. G.; Bookhagen, B.; Scherler, D.; Tofelde, S.; Alonso, R. N.; Kubik, P. W.; Binnie, S. A.; Strecker, M. R. (My University, 2016)
Fluvial fill terraces preserve sedimentary archives of landscape responses to climate change, typically over millennial timescales. In the Humahuaca Basin of NW Argentina (Eastern Cordillera, southern Central Andes), our 29 new optically stimulated luminescence ages of late Pleistocene fill terrace sediments demonstrate that the timing of past river aggradation occurred over different intervals on the western and eastern sides of the valley, despite their similar bedrock lithology, mean slopes, and precipitation. In the west, aggradation coincided with periods of increasing precipitation, while in the east, aggradation coincided with decreasing precipitation or more variable conditions. Erosion rates and grain size dependencies in our cosmogenic Be-10 analyses of modern and fill terrace sediments reveal an increased importance of landsliding compared to today on the west side during aggradation, but of similar importance during aggradation on the east side. Differences in the timing of aggradation and the Be-10 data likely result from differences in valley geometry, which causes sediment to be temporarily stored in perched basins on the east side. It appears as if periods of increasing precipitation triggered landslides throughout the region, which induced aggradation in the west, but blockage of the narrow bedrock gorges downstream from the perched basins in the east. As such, basin geometry and fluvial connectivity appear to strongly influence the timing of sediment movement through the system. For larger basins that integrate subbasins with differing geometries or degrees of connectivity (like Humahuaca), sedimentary responses to climate forcing are likely attenuated.
Citation: Schildgen, T. F., Robinson, R. A. J., Savi, S., Phillips, W. M., Spencer, J. Q. G., Bookhagen, B., . . . Strecker, M. R. (2016). Landscape response to late Pleistocene climate change in NW Argentina: Sediment flux modulated by basin geometry and connectivity. Journal of Geophysical Research-Earth Surface, 121(2), 392-414. doi:10.1002/2015jf003607
Keywords: Berylium-10; Optically Stimulated Luminescence; Humahuaca Basin; South; American Monsoon System; Fluvial Terraces